Physiological Changes in Hypertension in the Elderly Effected by the Combination of SEGROTAK (Ergonomics and Brain Gymnastics) - Faisnani Yogi Rochmah; Isna Hikmawati; Mustiah Yulistani; Wahyu Riyaningrum (Proceedings Series on Health & Medical Sciences, 2024)
Background: Hypertension is one of the most common diseases in Indonesia and often occurs in the elderly due to a decrease in the body's physiology. In 2021, the number of hypertension sufferers in Banyumas will be 129,817 from a total of 40 villages. There were 4,435 people who handled hypertension at Kembaran Health Center 1. Physical activity such as gymnastics is important for the elderly to do to maintain physiological function so that it can optimize the function of various systems of the elderly body, one of which is useful for lowering blood pressure. Method: This study used a pre-experimental design type of one-group pretest-posttest.The population in this study were hypertensive elderly who were active in elderly integrated health center in Linggasari Village. This study used a total sampling technique, and the sample used was 36 respondents. Results: The results of the paired t test showed a decrease in systolic and diastolic pressure after exercise (p value 0.000). The results of the Wilcoxon test showed a pulse rate of 0.018, oxygen saturation of 0.000 (SPO2), respiratory rate of 0.001, and complaints of joint pain of 0.000. Conclusion:In this study, it can be concluded that there is a significant effect of SEGTOTAK exercise on the physiological changes in the elderly with hypertension.